The Role of Internal Capabilities in Driving the Financial Sustainability of SMEs: A Resource Based View Perspective - Hamzah, Amir (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
This study aims to examine the influence of budget planning, financial literacy, accounting literacy, and access to finance on the financial sustainability of Small and Medium Enterprises (SMEs) in Kuningan Regency. Motivated by the challenges faced by SMEs in ensuring long-term financial viability, this research adopts the Resource-Based View (RBV) theory to explore how internal capabilities contribute to sustainable business performance. Using a quantitative approach, data were collected through surveys involving 108 SMEs selected via simple random sampling. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The findings reveal that budget planning, financial literacy, and access to finance have a significant positive impact on financial sustainability. However, accounting literacy does not show a significant influence. These results highlight the importance of strengthening internal competencies to improve SME financial resilience. The study contributes to the literature by integrating internal capability variables within the RBV framework and offers practical insights for SME development strategies in similar regional contexts. Keywiords: SMEs; Budget Planning; Financial Literacy; Access to Finance; Financial Sustainability